Identifying nonalcoholic fatty liver disease patients with active fibrosis by measuring extracellular matrix remodeling rates in tissue and blood. Issue 1 (15th November 2016) - Decaris, Martin L.; Li, Kelvin W.; Emson, Claire L.; Gatmaitan, Michelle; Liu, Shanshan; Wang, Yenny; Nyangau, Edna; Colangelo, Marc; Angel, Thomas E.; Beysen, Carine; Cui, Jeffrey; Hernandez, Carolyn; et al.
Abstract : Excess collagen synthesis (fibrogenesis) in the liver plays a causal role in the progression of nonalcoholic fatty liver disease (NAFLD). Methods are needed to identify patients with more rapidly progressing disease and to demonstrate early response to treatment. We describe here a novel method to quantify hepatic fibrogenesis flux rates both directly in liver tissue and noninvasively in blood. Twenty‐one patients with suspected NAFLD ingested heavy water ( 2 H2 O, 50‐mL aliquots) two to three times daily for 3‐5 weeks prior to a clinically indicated liver biopsy. Liver collagen fractional synthesis rate (FSR) and plasma lumican FSR were measured based on 2 H labeling using tandem mass spectrometry. Patients were classified by histology for fibrosis stage (F0‐F4) and as having nonalcoholic fatty liver or nonalcoholic steatohepatitis (NASH). Magnetic resonance elastography measurements of liver stiffness were also performed. Hepatic collagen FSR in NAFLD increased with advancing disease stage (e.g., higher in NASH than nonalcoholic fatty liver, positive correlation with fibrosis score and liver stiffness) and correlated with hemoglobin A1C. In addition, plasma lumican FSR demonstrated a significant correlation with hepatic collagen FSR. Conclusion : Using a well‐characterized cohort of patients with biopsy‐proven NAFLD, this study demonstrates that hepatic scar in NASH is actively remodeled even in advanced fibrosis, a disease that is generally regarded as static and slowly progressive. Moreover, hepatic collagen FSR correlates with established risks for fibrotic disease progression in NASH, and plasma lumican FSR correlates with hepatic collagen FSR, suggesting applications as direct or surrogate markers, respectively, of hepatic fibrogenesis in humans. (Hepatology 2017;65:78‐88).